1993
DOI: 10.1213/00000539-199305000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes During Laparoscopic Cholecystectomy

Abstract: Hemodynamics during laparoscopic cholecystectomy under general anesthesia (isoflurane in N2O/O2 (50%)) were investigated in 15 nonobese ASA Class I patients by using invasive hemodynamic monitoring including a flow-directed pulmonary artery catheter. During surgery, intraabdominal pressure was maintained automatically at 14 mm Hg by a CO2 insufflator, and minute ventilation was controlled and adjusted to avoid hypercapnia. Hemodynamics were measured before anesthesia, after the induction of anesthesia, after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
279
4
33

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(329 citation statements)
references
References 0 publications
13
279
4
33
Order By: Relevance
“…Clinical studies during intraperitoneal insufflation with carbon dioxide showed that arterial blood pressure increases and cardiac output decreases [8,13]. Few data exist on the hemodynamic effects of laparoscopy in an extraperitoneally created cavity.…”
mentioning
confidence: 99%
“…Clinical studies during intraperitoneal insufflation with carbon dioxide showed that arterial blood pressure increases and cardiac output decreases [8,13]. Few data exist on the hemodynamic effects of laparoscopy in an extraperitoneally created cavity.…”
mentioning
confidence: 99%
“…Traditionally, they have been used as antihypertensive drugs, but doses based on sedative, anxiolytic, analgesic properties are being developed. (13,14,15) We studied 100 adult patients with similar Demographic profiles like Age, Height, Weight, BMI, Sex, ASA physical status I and II and scheduled for elective laparoscopic cholecystectomy under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…As a generalisation, pneumoperitoneum orchestrates a neurohormonal stress response which LVEF: left ventricular ejection fraction increases systemic vascular resistance, mean arterial blood pressure and heart rate [13][14][15]. These factors increase the afterload and myocardial oxygen consumption which are poorly tolerated by patients with cardiac dysfunction [16].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ischemic heart disease are prone to develop atrial fibrillation, a condition which could be precipitated by CO 2 pneumoperitoneum [19]. Most of the studies addressing cardiovascular effects of CO 2 pneumoperitoneum have been performed in healthy subjects, who seem to tolerate pneumoperitoneum without untoward problem [14,15,20]. Similar issues have not been studied under the setting of randomized trial in patients with cardiac co-morbidities [21].…”
Section: Discussionmentioning
confidence: 99%